Handwritten Digital Signatures Accuracy Enhancement Comparison on Android-Based Mobile Application Systems - Rohajawati, Siti; Ismail , Aditya; Gunawan, Irwan Prasetya; Sitorus, Brian Arnesto (Indonesian Journal of Information Systems, 2024)
The research reported in this paper aimed to improve the quality, size ratio, and storage size of Digital Signatures (DS) used in the e-form Fumida app, a mobile application employed by PT Fumida Pestindo Jaya (Fumida) pest control, termite control, and fumigation services for data collection and verification. The application was developed using MADLC method for research and development of mobile application and utilized as a replacement for paper media used to fill in data related to work with the DS feature (e-signature), from which verification/authentication of the work results carried out by Fumida to its clients is given. The original DS, while replacing paper forms, suffered quality and accuracy loss when resized for printing, prompting the investigation of three methods to enhance their integrity. This process was subsequently examined using a questionnaire with the help of 22 respondents and calculation of questionnaire data. The results of our study showed that our model 3 emerged as the most effective solution, maintaining high image quality and accuracy even when resized.